(untitled) (Revista da Tulha, 2015)
In a technological and computerized twenty-first century world, narcissistic and hedonic (LIPOVETSKY, 2005), the standardization of mass consumption (Adorno, 1941) led to a “dressage” in perception, besides a changing of parameters, attributes of expression and principles of musical poetics that make up the structural dimensions of music, by promoting an almost permanent state of distraction and entertainment, diverging of the concentrated listening which allows to articulate, interpret, understand and build a thought from what is heard. This new perception had significant impact on the habits of listening in the area of education and of musical training. How then act in the educational context of mainstream education and teaching music in a society immersed in sensory training for consumption? In this article we discuss and point out alternatives to retake the concentration and the conscious effort of perception, analysis, interpretation and understanding for a critical thinking.